APPLICATION OF WASTE BANK AS A SOLUTION TO IMPROVE CLEAN AND HEALTHY LIVING BEHAVIOR IN THE MUHAMMADIYAH MOSQUE ENVIRONMENT, PUTAT VILLAGE, SIDOARJO REGENCY - Azizah, Nurul (Antis-publisher, 2026)
Objective: The objective of this study is to implement the concept of a waste bank as a novel solution to enhance clean and healthy living behaviors within the mosque environment. Method: The method employed in this study commenced with the delivery of PHBS education, followed by the implementation of PHBS practices, and culminated in the provision of a waste bank inventory. Results: The results of the study indicate an increase in awareness and participation among mosque members in maintaining cleanliness and effective waste management. This, in turn, supports a healthy and comfortable mosque environment for worship. Novelty: The promotion of clean and healthy living behaviors is of paramount importance for the enhancement of public health, particularly in places of worship such as mosques. The Muhammadiyah Mosque in Putat Village, Sidoarjo Regency, is confronted with challenges in waste management that have a detrimental effect on the cleanliness and comfort of the surrounding environment.